Complement activation in the plasma and placentas of women with different subsets of antiphospholipid syndrome. (16th September 2019) - Scambi, Cinzia; Ugolini, Sara; Tonello, Marta; Bortolami, Oscar; De Franceschi, Lucia; Castagna, Annalisa; Lotti, Virginia; Corbella, Michela; Raffaelli, Ricciarda; Caramaschi, Paola; Mattia, Elena; Biasi, Domenico; et al.
Abstract: Problem: As antiphospholipid antibody‐positive women with adverse pregnancy outcomes have higher plasma complement activation product levels, and the placentas of women with antiphospholipid syndrome (APS) exhibit C4d complement component deposition, complement activation involvement has been hypothesized in APS pregnancy complications. Method of study: Plasma levels of C5a and C5b‐9 complement components of 43 APS non‐pregnant patients and 17 pregnant APS women were measured using enzyme‐linked immunosorbent assay. The results were compared with those of 16 healthy non‐pregnant women and eight healthy pregnant women, respectively. Placenta samples of five APS patients at high risk of pregnancy complications and of five healthy controls were subjected to immunoblotting analysis with specific antibodies to C5b‐9 and CD46, CD55, CD59 complement regulators. Results: The mean plasma C5a and C5b‐9 levels were significantly higher in the non‐pregnant APS patients with previous thrombosis ± pregnancy morbidity ( P = .0001 and P = .0034, respectively) and in the pregnant APS women with adverse outcomes ( P = .0093 for both). Similarly, C5b‐9 amounts were significantly higher in the adverse pregnancy outcome placenta ( P = .0115) than in those associated to a favorable outcome. The mean CD46, CD55 and CD59 amounts were, instead, lower, although not always significantly, in the placentas of all the high‐risk APS women with respect to the control placentas. Conclusion: Data analysis demonstrated that there was significant complement activation in the more severe subset of APS patients and in only the adverse pregnancy outcome APS women. Further studies will clarify whether the lower CD46, CD55, and CD59 expressions in the APS placentas are limited to only high‐risk APS patients.